Small and Historic Cities of Zabaikalye: Architectural Heritage of Troitskosavsk-Kyakhta - Kradin, Nikolai (project baikal, 2020)
Architecture of one of the small historic cities of Transbaikalia, Kyakhta is considered. The author analyzes the nature of the Kyakhta buildings, historical and architectural monuments, notes the uniqueness and unusualness of this border settlement in the south of Buryatia. The tea route from China to Europe became the basis for the construction of the corresponding buildings and complexes here. Rich in historical events and cultural monuments, Kyakhta is of constant interest among local and foreign researchers.
Keywords: building; Savva Raguzinsky; Trinity Cathedral; P.S. Pallas; A.M. Lushnikov; outpost